The given information is:
-S varies inversely as G.
-When G is 4.2, S is 7.
As the varies inversely, then it can be expressed as:
![S=(k)/(G)](https://img.qammunity.org/2023/formulas/mathematics/college/z1roft2cmvymz1r03jemxqu9d9yphxa1ob.png)
Where k is the constant of variation.
We can find k by replacing S=7 and G=4.2:
![\begin{gathered} 7=(k)/(4.2) \\ k=7*4.2 \\ k=29.4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/j65zgvbms55dd8jz3t5fzlfmqxkxzm8ny7.png)
Thus, when G is 6, we can solve for S by using the constant value k:
![\begin{gathered} S=(29.4)/(6) \\ S=4.9 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/r1tyositx44ebu68yo938k5lxfgjrc5op8.png)
The answer is when G=6, then S=4.9